ВЛИЯНИЕ КУЛЬТУРНЫХ РАЗЛИЧИЙ НА РЕЧЕВОЕ ПОВЕДЕНИЕ УЗБЕКСКИХ СТУДЕНТОВ В КОНТЕКСТЕ ОБУЧЕНИЯ ИНОСТРАННОМУ ЯЗЫКУ - Зияева, С.А. (SCIENCE and SOCIETY, 2023)
This article is devoted to the study of the influence of cultural differences on the speech behavior of Uzbek students in the context of foreign language teaching. The problem addressed by this study is that despite the fact that foreign language teaching is becoming increasingly popular and in demand in the world, it often encounters difficulties in mutual understanding between teachers and students due to cultural differences.
Keywords: speech behavior; dominant features of communication; mentality; communicative conflict; national and cultural specificity; the expression of politeness; the effectiveness of teaching